2011
DOI: 10.1139/g11-042
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale development of functional markers inBrassicaspecies

Abstract: Numerous quantitative trait loci (QTL) have been detected in Brassica species, but fine-mapping of major QTL has advanced slowly. The development of functional markers can overcome this barrier. We used publicly available PlantGDB-assembled unique transcripts (PUTs) from Brassica species to design 7836 functional simple sequence repeat (SSR) primer pairs. Functional annotation of the PUTs containing SSRs was done by Blast2GO. The PUTs harbouring SSRs were mainly involved with nucleotide or protein binding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…We found that 60% of SSR primer pairs exhibited polymorphic bands in the different Brassica species (An et al. ), similar to the 60–73% polymorphism detected for other developed SSR primers in Brassica species (Lowe et al. , Piquemal et al.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We found that 60% of SSR primer pairs exhibited polymorphic bands in the different Brassica species (An et al. ), similar to the 60–73% polymorphism detected for other developed SSR primers in Brassica species (Lowe et al. , Piquemal et al.…”
Section: Discussionsupporting
confidence: 84%
“…We used the same set of experimental materials (15/16 accessions) in another study (An et al. ) to estimate the utility of functional SSR markers developed from assembled unique transcripts. We found that 60% of SSR primer pairs exhibited polymorphic bands in the different Brassica species (An et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Although several studies have been conducted to develop genic SSR markers from the ESTs/unique transcripts of B. rapa , 29,31,32 B. oleracea 31 and B. napus , 3032 the total number (<5000) of publicly available genic SSR markers has remained limited in Brassica (). In the current study, a large number of newly developed genome-wide SSR markers (32 648, 33 228 and 58 952 for B. rapa , B. oleracea and B. napus , respectively) were involved in the annotated genes (Supplementary Table S7) and thus belonged to the genic SSR markers.…”
Section: Discussionmentioning
confidence: 99%